Comparative analysis of Helix pomatia L. shells found in soils with varying degrees of contamination (southern Poland) - Aleksander-Kwaterczak, Urszula; Gołas-Siarzewska, Magdalena (Geology, Geophysics and Environment, 2016)
Soil samples and snails - Helix pomatia (Linnaeus, 1758) specimens were collected from the region of Lesser Poland. Research based on soil from this area showed a differentiated degree of environmental contamination, which influenced the composition of elements that build mollusc shells. Concentrations of Pb, Mn, Cd, Fe, Zn and Cu in the snail shells and soil varied between localities. The highest of these concentrations were found in the soil in the city of Cracow. They were higher than those measured in the regions outside the city, 7 times in the case of Cd, and up to 123 times higher for Cu. Positive association between soil pollution and shell contamination can be observed (rs≈0.9). A high concentration of metals in the environment and their bioavailability causes long-term accumulation of these elements in Helix pomatia shells.